Development, change, and gender in Cairo : a view from the household - Singerman, Diane; Hoodfar, Homa. (Bloomington : Indiana University Press, 1996)
Presents essays that focus on the Egyptian household as the key institution for understanding the dynamics of political, economic, and social change. This collection exposes the complexity of social issues in Cairo, and explains why household economics have become increasingly politicized for the Egyptian population
Survival strategies and the political economy of low-income households in Cairo / Homa Hoodfar -- Transforming women's identity : the intersection of household and workplace in Cairo / Arlene Elowe MacLeod -- Egyptian male migration and urban families left behind : "feminization of the Egyptian family" or a reaffirmation of traditional gender roles? / Homa Hoodfar -- What's the use? the household, low-income women, and literacy / K.R. Kamphoefner -- The state, urban households and management of daily life : food and social order in Cairo / Nadia Khouri-Dagher -- Beyond paradigms of development : a pragmatic response to housing needs in Cairo's inner city / Nawal Mahmoud Hassan -- The family and community as politics : the popular sector in Cairo / Diane Singerman.
Includes bibliographical references and index.
Keywords: Households -- Economic aspects -- Egypt -- Cairo Region; Social change -- Egypt -- Cairo Region; Poor -- Egypt -- Cairo Region; Women -- Employment -- Egypt -- Cairo Region; Sex role -- Egypt -- Cairo Region; Women -- Egypt -- Cairo Region -- Social conditions